2015
DOI: 10.1016/j.foodhyd.2015.02.040
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pectin on in vitro β-carotene bioaccessibility and lipid digestion in low fat emulsions

Abstract: 11Soluble fibers, like pectin, are known to influence the physicochemical processes during the digestion 12 of dietary fat and may therefore affect the absorption of lipophilic micronutrients such as 13 carotenoids. The objective of the current work was to investigate whether the pectin concentration 14 and degree of methyl-esterification (DM) influence the bioaccessibility of carotenoids loaded in the 15 oil phase of oil-in-water emulsions. The in vitro β-carotene bioaccessibility was determined for 16 differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…It seems that the β‐carotene bioaccessibility increased if the lipid digestion increased, although the magnitude to which the increase occurred was different. Both results were also found by Verrijssen and others (). Therefore, the following hypothesis can be stated.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It seems that the β‐carotene bioaccessibility increased if the lipid digestion increased, although the magnitude to which the increase occurred was different. Both results were also found by Verrijssen and others (). Therefore, the following hypothesis can be stated.…”
Section: Resultssupporting
confidence: 88%
“…First, smaller oil droplets were found in the CP57 emulsion (median ( = D[v; 0.5]) of 1.8 μm and D[v; 0.9] of 4.2 μm) compared to oil droplets in the CP30 emulsion (median of 5.5 μm and D[v; 0.9] of 17.4 μm; Figure A and confirmed by microscopy [results not shown]), so it seems that CP57 had a better emulsifying capacity compared to CP30. Probably in CP57, the block‐wise patterns of hydrophilic and hydrophobic groups of the GalA‐molecules (at pH 6) emulsified better compared to the more hydrophilic molecules in CP30 (Fraeye and others ; Verrijssen and others ). It can be concluded that the DM in the CP emulsions is important for the oil droplet size distribution.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this regard, the higher DM of pectin in unripe tomatoes could hinder the incorporation of carotenoids into micelles resulting in lower bioaccessibility. Similar results were found by Verrijssen, Verkempinck, Christiaens, Van Loey, and Hendrickx (2015) who reported an increase of the incorporation of β-carotene into the micelles by decreasing the pectin DM of the emulsions. In addition, the depolymerization process could also facilitate the disruption of cell walls during digestion, allowing the release of carotenoids from tomato matrix and promoting their micellar solubilization (Ornelas-Paz et al, 2008).…”
Section: Bioaccessibility Of Carotenoidssupporting
confidence: 90%
“…Emulsion-based delivery systems can be produced using various emulsification processes and they have been widely used to protect bioactive compounds such as carotenoids from degradation, ameliorate its dispersion in an aqueous media, and increase its bioaccessibility [10][11][12][13][14][15][16]. However, in the last years, oil droplet reduction in the range of 20-500 nm [17] showed several advantages over conventional emulsions.…”
Section: Introductionmentioning
confidence: 99%